ANALISIS IMPLEMENTASI KEBIJAKAN UNDANG-UNDANG NOMOR 18 TAHUN 2017 PASAL 21 TENTANG PERLINDUNGAN PEKERJA MIGRAN INDONESIA SELAMA BEKERJA DI LUAR NEGERI - Muhammad Emir Al-Azkiya (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2022)
Indonesian Migrant Workers with the acronym PMI are one of the drivers of the Indonesian economy, in line with this BPS (Central Bureau of Statistics) and the Ministry of Industry in 2017 explained that PMI services are the 6th largest foreign exchange earner in Indonesia, with a contribution of IDR 140 trillion. Although PMI has an extraordinary role in Indonesia, such as increasing foreign exchange income, in fact it has a large complexity of dynamics of problems as well. Such as persecution, unpaid salaries, and many more. This study aims to analyze the policy implementation process of Law no. 18 of 2017 PMI protection in article 21 related to protection while working abroad. The results of this study indicate the implementation of policies in Law no. 18 Th. 2017 in article 21, is not yet fully optimal. This can be seen from the many PMI problems that have not been resolved to the number of problematic PMIs who are reluctant to be repatriated.